Experimental and numerical evaluations of Kirkuk field soil treated with waste shredded tire - Mohammed Raheem, Aram (International Journal of Engineering and Technology, 2018)
In this study, an experimental and numerical investigation of Kirkuk real field soil treated with waste tire has been examined. Field soil samples from Kirkuk city have been collected and tested experimentally to evaluate the basic soil properties. The field soil has been treated with waste shredded tires and up to 10%. A series of direct shear tests under different normal stresses and unconfined compression tests with two different rates have been performed on both untreated and waste tire treated soils. For the untreated soil, the maximum shear stress measured by the direct shear test increased by 150% when the normal shear stress increased from 50 kPa to 150 kPa. For the 5% and 10% waste tire treated soils, the maximum shear stresses measured by the direct shear test increased by 110% and 105% when the normal stress increased from 50 kPa to 150 kPa respectively. The peak uniaxial stress measured by the unconfined compression test increased by 83% and 98% as the waste tire treatment increased from 0% to 10% for both testing rates of 0.125 mm/min and 0.25 mm/min respectively. Finally, finite element method using three different models represented by elastic, hyperbolic and Mohr-Coulomb elastic-plastic models have been used to model unconfined compression tests for both untreated and 10% waste tire treated soils. For both untreated and waste tire treated soils, the elastic model over predicted the shear stress versus shear strain relationship whereas the elastic-plastic model had a very good agreement with the experimental data. However, the hyperbolic model had a good prediction for the initial part of the shear stress versus shear strain relationship for both untreated and waste tire treated soils with an overestimation for the second part of the experimental data.Â Â